[Aerial view of a hotel in Barbados] - (:unkn) unknown (1964, 2010)
Photo of a hotel in Barbados. There is a view of the airport runway in the background. The postcard bears a handwritten correspondence describing the writer's stay at the hotel and also includes a 12 cents Trinidad and Tobago postage stamp.
Colour: Black and White ; Style: Landscape ; Other: Bordered, Undivided
Keywords: Barbados; Postcards; Hotels--Barbados; Airports--Barbados; Runways (Aeronautics)--Barbados